Assessment of Fodder Production Potential of Lucerne (Medicago sativa L.,) Genotypes for Sustainable Live stock Production - T. Shashikala; R. Susheela; R. V. T. Balazzii Naaiik; M. Shanti; B. Murali; V. Chandrika (International Journal of Economic Plants)
The present study was conducted with Nine genetically diverse and improved perennial cultures of Lucerne along with two national checks were studied in randomized block design with three replications  at AICRP on Forage Crops, Hyderabad continuously for three years i.e from Rabi 2010-11, 2011-12 and 2012-13. The national checks include Anand-2 and RL-88. Nine genetically diverse and improved perennial cultures of Lucerne along with two national checks were studied in randomized block design with three replications at AICRP on Forage Crops, Hyderabad continuously for three years i.e from rabi 2010-11, 2011-12 and 2012-13. The results revealed that the entries registered highly significant differences among themselves for all the characters except crude protein content in all the years. The results revealed that  the entry RLH-4 recorded highest green fodder yield of 237.4 q ha-1, 297.1 q ha-1 and 273.5 q ha-1 respectively  for three consecutive years ,while for dry fodder and crude protein the entry RLH-5 showed superior performance of 82.5 q ha-1  & 17.3 q ha-1 respectively in 1st year of testing. However in 2nd and 3rd year again RLH-4 maintained significant superiority for both dry fodder (62.5 q ha-1, 57.5 q ha-1 respectively) and crude protein (13.4 q ha-1, 12.2 q ha-1 respectively) yields. The results also inferred that the check variety Anand-2 is suitable to cultivate as annual fodder legume, while RL-88 occupies place in perennial fodder legumes.